Bioinformatics Approaches to Predict Mutation Effects in the Binding Site of the Proangiogenic Molecule CD93 - Cicaloni, Vittoria; Karmakar, Malancha; Frusciante, Luisa; Pettini, Francesco; Visibelli, Anna; Orlandini, Maurizio; Galvagni, Federico; Mongiat, Maurizio; Silk, Michael; Nardi, Federica; Ascher, David; Santucci, Annalisa; et al. (Frontiers in Bioinformatics, 2022)
The transmembrane glycoprotein CD93 has been identified as a potential new target to inhibit tumour angiogenesis. Recently, Multimerin-2, a pan-endothelial extracellular matrix protein, has been identified as a ligand for CD93, but the interaction mechanism between these two proteins has still to be clarified. In this paper, we aim to investigate the structural and functional effects of induced mutations on the binding domain of CD93 to Multimerin-2. Starting from experimental data, we assessed how specific mutations in the C-type lectin-like domain (CTLD) affect the binding interaction profile. We described a four-steps workflow in order to predict effects of variations on the inter-residue interaction network at the PPI, based on evolutionary information, complex network metrics and energetic affinity. We showed that the application of computational approaches, combined with experimental data, allowed us to gain more in-depth molecular insights into the CD93/Multimerin-2 interaction, offering a platform for developing innovative therapeutics able to target these molecules and block their interaction. This comprehensive molecular insight might provide a useful tool to drug design in cancer therapy